MECHANISMS FOR DEVELOPING DISTANCE EDUCATION IN THE DIGITAL WORLD (World Bulletin of Education and Learning, 2025)
This article discusses the relationship between teacher and student in the development of distance education, as well as methods for assessing assimilation. Furthermore, the current state and problems of distance learning are examined.
Keywords: Digital technologies, information and communication technologies, modern education, digital knowledge, Internet system, distance learning.